2014 Physics Education Research Conference Proceedings 2015
DOI: 10.1119/perc.2014.pr.020
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction and Perceptions of Instructor Support in Studio Physics

Abstract: Abstract. This study investigates the pedagogical factors that impact students' satisfaction with studio-style physics courses. Students enrolled in various sections of a SCALE-UP style course at EKU (N=184) responded to a reformed version of the Pedagogical Expectancy Violation Assessment (PEVA) and a course satisfaction questionnaire. Within the PEVA, students identified their satisfaction with particular activities based on how often they expected them to occur or how often they had experienced them. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Because we were concerned with course satisfaction at week 14, we investigated the three factors generated from students' reported experiences in the course (Table 2). Doing so is consistent with previous analyses [3,4].…”
Section: B Course Satisfactionsupporting
confidence: 82%
See 3 more Smart Citations
“…Because we were concerned with course satisfaction at week 14, we investigated the three factors generated from students' reported experiences in the course (Table 2). Doing so is consistent with previous analyses [3,4].…”
Section: B Course Satisfactionsupporting
confidence: 82%
“…The instructor providing guidance for how to do activities 14. Presenting my problem solutions to the class In previous studies, we found that the better the students felt about how each cluster of related activities was implemented, the higher their overall satisfaction in the course [4]. However, we were unable to disentangle whether the students enjoyed the activity itself or rather were pleased by how often they experienced it.…”
Section: Theorymentioning
confidence: 53%
See 2 more Smart Citations
“…After modifying the measure somewhat (see Refs. [32,33], and [17] for details on revisions to the PEVA), we used a factor analysis to determine that the frequency with which students reported experiencing the activities clustered into four factors. By looking at the activities that principally loaded onto each factor, we identified these factors as related to instructor support, instructor-led class time, working with classmates, and working individually.…”
Section: Pevamentioning
confidence: 99%